Lettiske Waffen-SS-soldater i Danmark efter 2. Verdenskrig - Clausen, Henrik (Fra Krig og Fred, 2026)
Baltic refugees in Denmark after the Second World War has been little researched despite the many interesting aspects of this subject. they were regarded as Soviet citizens by the Soviet Union, but the British, however, did regard them as stateless because the United Kingdom did not recognize the Soviet annexation of the Baltic states. In this article I am examining how Denmark as a small state caught between the United Kingdom and the Soviet Union dealt with the Baltic refugees. The Baltic refugees were treated according to guidelines put down by the SHAEF representation in Denmark (later the British Military Mission). This excluded them from being repatriated to the Soviet Union contrary to the Soviet citizens which were quickly repatriated. The Soviet-Danish relationship was strained by Soviet demands for having more citizens returned and a Soviet quid-pro-quo policy. However, there was never a formal demand from the Soviet ministry of foreign affairs to have the Balts extradited. Denmark pursued in the Early Cold War (1945-1949) a policy of “bridgebuilding” between East and West. Denmark relied heavily on United Kingdom but feared the intentions of the Soviet Union. The Danish approach was very different to that of Sweden who during WW2 built up a considerable military defensive capability. About 30,000 Baltic refugees fled to Sweden but the Soviet Union stopped demanding their extradition in March 1946. The Danish refugee policy was to get rid of as many refugees as possible, including the Baltic refugees. Denmark succeeded in this: Only about 400 Baltic refugees remained in Denmark. Some of the Baltic refugees had served as soldiers in the German armed forces in different capacities – ranging from combat troops in the Waffen-SS over police troops to members of construction battalions. The Danish authorities did not investigate if any of these former soldiers had committed war crimes. Danish newspapers show that there was sympathy towards the Baltic refugees in the Danish population - apart from Land og Folk, published by the Danish communist party and loyal to Moscow. My research concludes that there is no sign of the Danish authorities contemplating to hand over the Baltic refugees to the Soviet Union despite the goal of getting rid of all refugees in Denmark. This was not done out of humane considerations but because Denmark strictly adhered to the British guidelines on refugees and to the UN resolution of 1946 on refugees.